Theoretical Evaluation of Silicon Crystal Growth Using Gallium Solvent - Alijon Razzokov; Eshchanov, Khushnudbek (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Semiconductor materials are of great importance throughout the world. Silicon crystals are this field's most widely used and relatively inexpensive material. Obtaining low-dislocation and defect-free silicon crystals is one of the current issues, and we theoretically investigated the production of low-defect silicon crystals from silicon-gallium melt. We considered the defects that appear in the silicon crystals grown from the solution related to the large-sized silicon nanoclusters involved in the crystal formation based on the obtained results, we showed the conditions for obtaining silicon crystals with few defects from the silicon-gallium solution.